2015
DOI: 10.1007/s00436-015-4765-8
|View full text |Cite
|
Sign up to set email alerts
|

Parasites and vector-borne pathogens in client-owned dogs in Albania. Blood pathogens and seroprevalences of parasitic and other infectious agents

Abstract: Knowledge on the epidemiology of parasitic and vector-borne infections is still very limited for Albania, a country located in the Balkan Peninsula in southeast Europe. Recent publications indicated prevalence rates of up to 52% for vector-borne infections in less-cared dogs in Albania. To provide data on the epidemiological situation in dogs under veterinary care, a total of 602 client-owned dogs presented to four small animal clinics between March 2010 and April 2011 in Tirana, Albania, were screened by exam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(16 citation statements)
references
References 78 publications
1
13
2
Order By: Relevance
“…Findings of (Hamel et al, 2015) were not in agreement with the results of the present study who reported 24% prevalence of anaplasma species. Higher prevalence in the present study might be due to the fact that Peshawar and Charsadda districts offer favorable environment for tick infestation and tick borne diseases in other domestic animals.…”
Section: Risk Factors For Haemo-parasitescontrasting
confidence: 57%
“…Findings of (Hamel et al, 2015) were not in agreement with the results of the present study who reported 24% prevalence of anaplasma species. Higher prevalence in the present study might be due to the fact that Peshawar and Charsadda districts offer favorable environment for tick infestation and tick borne diseases in other domestic animals.…”
Section: Risk Factors For Haemo-parasitescontrasting
confidence: 57%
“…Co-infection by T. gondii and Anaplasma has been reported in rodents [ 27 ], dogs [ 10 ], ticks [ 35 ], and wild boars [ 22 ]. However, a survey on the occurrence of goats co-infected by T. gondii and Anaplasma was only reported in Slovakia [ 8 ].…”
Section: Resultsmentioning
confidence: 99%
“…10.3 and 11.3% respectively [30, 31]. Other studies from the Balkan Peninsula have indicated an overall prevalence of CVBDs ranging from 25.7% in Croatia to 25.1% in Albania [32, 33]. Higher prevalence rates have been observed in Spain (37.1%) [34] and Portugal (66%) [35].…”
Section: Discussionmentioning
confidence: 99%